Stereolithography of SiOC Ceramic Microcomponents. Issue 2 (6th November 2015) - Zanchetta, Erika; Cattaldo, Marco; Franchin, Giorgia; Schwentenwein, Martin; Homa, Johannes; Brusatin, Giovanna; Colombo, Paolo
Abstract : The first example of the fabrication of complex 3D polymer‐derived‐ceramic structures is presented with micrometer‐scale features by a 3D additive manufacturing (AM) technology, starting with a photosensitive preceramic precursor. Dense and crack‐free silicon‐oxycarbide‐based microparts with features down to 200 μm are obtained after pyrolysis at 1000 °C in a nitrogen atmosphere.